2008
DOI: 10.1111/j.1445-6664.2008.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, mineral content, and antioxidant properties of 14 Mexican weeds used as fodder

Abstract: Many wild weeds are used in Mexico as fodder. Due to their economic value, this investigation was undertaken to determine the chemical composition of 14 species. The mineral, crude protein, fiber, and total phenolic content, as well as the antioxidant activity, was determined. There was a significant variation in the mineral content among the 14 weeds, which all had calcium and potassium as the predominant elements. According to the results, some of the weeds might represent possible mineral deficiency sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
10
1
1
Order By: Relevance
“…Species of quelites with edible leaves, flowers, vines and stems contribute a significant amount of carbohydrates, fats, dietary fiber, protein, vitamins and minerals to the diet. For example, in the genera Amaranthus , Chenopodium , Begonia , Crotalaria , Anoda , Cyclanthera , Calandrinia , Porophyllum , Taraxacum , Tinantia , Xanthosoma , Lippia , Piper , Peperomia and Galinsoga , the protein content varies from 2.7 to 44.2%, the fiber content reaches 22.7%, the ash content reaches 13.0% and the carbohydrate content reaches 56.8% (dry weight), with large variations within each genus and species [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. These characteristics make the proximate composition of quelites comparable to that of conventional leafy vegetables.…”
Section: Composition Of Edible Stems Leaves and Flowers Of Quelitmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of quelites with edible leaves, flowers, vines and stems contribute a significant amount of carbohydrates, fats, dietary fiber, protein, vitamins and minerals to the diet. For example, in the genera Amaranthus , Chenopodium , Begonia , Crotalaria , Anoda , Cyclanthera , Calandrinia , Porophyllum , Taraxacum , Tinantia , Xanthosoma , Lippia , Piper , Peperomia and Galinsoga , the protein content varies from 2.7 to 44.2%, the fiber content reaches 22.7%, the ash content reaches 13.0% and the carbohydrate content reaches 56.8% (dry weight), with large variations within each genus and species [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. These characteristics make the proximate composition of quelites comparable to that of conventional leafy vegetables.…”
Section: Composition Of Edible Stems Leaves and Flowers Of Quelitmentioning
confidence: 99%
“…One of the greatest contributions of edible leafy plants or quelites is their content of minerals such as K, Ca, Mg, P, S, Fe, Zn, Mn, Na, B, Mo, Cu and Co, which varies widely among the genera Amaranthus , Anoda , Begonia , Calandrinia , Chenopodium , Crotalaria , Cucurbita , Cyclanthera , Erythrina , Lippia , Phaseolus , Peperomia , Piper , Porophyllum , Portulaca , Suaeda , Tinantia , Tridax and Xanthosoma [ 32 , 40 , 43 , 49 , 53 , 54 , 57 , 58 , 59 ]. In the genera Amaranthus , Begonia , Cyclanthera , Cucurbita (leaves), Phytolacca , Piper , Porophyllum , Solanum and Tinantia , important amounts of vitamins A, B 1 , B 2 , B 3 , B 6 , E and C, as well as niacin, have been determined [ 35 , 39 , 43 , 50 , 55 ].…”
Section: Composition Of Edible Stems Leaves and Flowers Of Quelitmentioning
confidence: 99%
“…83, 82.82 ± 4.17 ug/mL, 76.63 ± 2.34 ug/mL, 12.86 ± 0.46% respectivamente (Wang et al 2017). En otro estudio realizado con Desmodium molliculum colectado en México mostró una actividad inhibidora de radicales libres con an IC50 of 221.30 mg mL -1 (Gutiérrez et al 2008) El efecto inhibitorio de la enzima aldosa reductasa le confiere a Desmodium molliculum una ligera capacidad (12.86%) de inhibir esta enzima que en condiciones de hiperglicemia se encarga de convertir monosacáridos como la glucosa en polialcoholes como el sorbitol, estos últimos son responsables de complicaciones diabéticas que dan lugar a daño microvascular al tejido nervioso y también a la retina y al riñón (Wang et al 2017, Shukla et al 2017.…”
Section: Actividad Anticonceptivaunclassified
“…The use of C. arvensis also has been explored for phytoremediation by heavy metal accumulation (Cruz-Jiménez et al, 2005;Gardea-Torresdey, Peralta-Videa, Montes, de la Rosa, & Corral-Díaz, 2004;Montes, Peralta-Videa, Parsons, Corral Díaz, & Gardea-Torresdey, 2013;Montes-Holguin et al, 2006). A similar pattern of studies as that found with correhuela is the one with Johnson grass (S. halepense) with studies on chemical control (Esqueda-Esquivel, Uresti-Durán, & Hernández-Aragón, 2015;Magallanes et al, 1986; Vera-Núñez, Grageda-Cabrera, Altamirano-Hernández, & Peña-Cabriales, 2010); biological control (Iracheta-Cárdenas, Galan-Wong, & Pereyra-Alferez, 1995;Martínez-Mendoza et al, 2012); and use as forage (Castro-González, Alayon-Gamboa, Ayala-Burgos, & Ramírez-Aviles, 2008;Gutiérrez et al, 2008;Ramírez-Vera et al, 2012).…”
Section: Control and Use Of Non-native Weedsmentioning
confidence: 99%